New α- and β-cyclodextrin derivatives with cinchona alkaloids used in asymmetric organocatalytic reactions - Tichá, Iveta Chena; Hybelbauerová, Simona; Jindřich, Jindřich (Beilstein Journal of Organic Chemistry, 2019)
The preparation of new organocatalysts for asymmetric syntheses has become a key stage of enantioselective catalysis. In particular, the development of new cyclodextrin (CD)-based organocatalysts allowed to perform enantioselective reactions in water and to recycle catalysts. However, only a limited number of organocatalytic moieties and functional groups have been attached to CD scaffolds so far. Cinchona alkaloids are commonly used to catalyze a wide range of enantioselective reactions. Thus, in this study, we report the preparation of new α- and β-CD derivatives monosubstituted with cinchona alkaloids (cinchonine, cinchonidine, quinine and quinidine) on the primary rim through a CuAAC click reaction. Subsequently, permethylated analogs of these cinchona alkaloid–CD derivatives also were synthesized and the catalytic activity of all derivatives was evaluated in several enantioselective reactions, specifically in the asymmetric allylic amination (AAA), which showed a promising enantiomeric excess of up to 75% ee. Furthermore, a new disubstituted α-CD catalyst was prepared as a pure AD regioisomer and also tested in the AAA. Our results indicate that (i) the cinchona alkaloid moiety can be successfully attached to CD scaffolds through a CuAAC reaction, (ii) the permethylated cinchona alkaloid–CD catalysts showed better results than the non-methylated CDs analogues in the AAA reaction, (iii) promising enantiomeric excesses are achieved, and (iv) the disubstituted CD derivatives performed similarly to monosubstituted CDs. Therefore, these new CD derivatives with cinchona alkaloids effectively catalyze asymmetric allylic aminations and have the potential to be successfully applied in other enantioselective reactions.
Keywords: asymmetric allylic amination; cinchona alkaloids; CuAAC click reaction; cyclodextrin; organocatalysts